Detection of GAD65 autoantibodies of type-1 diabetes using anti-GAD65-abs reagent produced from bovine brain tissue (Medical Journal of Indonesia, 2005)
Clinically, type 1 diabetes may presents as type 2 diabetes which sometimes not easily differentiated. Perhaps only autoimmune markers of β-cells destruction could differentiate those two clinical conditions. Due to extremely high cost ( $ 150/test), examination of anti-glutamic acid decarboxylase-65 auto-antibodies (anti-GAD65Abs) may not be routinely performed in most, if not all, clinical laboratories in Indonesia. Hence, the production of anti-GAD65 Abs reagent in Indonesia may reduce the cost and improve the quality of diabetes care in Indonesia. We produce reagent to detect anti-GAD65-Abs using bovine brain tissue as source of GAD enzyme in 3 steps. Step 1, isolation, purification of GAD65 from bovine brain tissue and used it as a primary antigen to stimulate the generation of anti-GAD65 antibodies in Wistar rat. Step 2, the purified GAD65 antibodies were than used as a secondary antibody to induce the production of anti-anti-GAD65-antibodies in Wistar rat and rabbit. Step 3. Labeling anti-antiGAD65-antibodies with alkaline phoshpatase and peroxidase, and detecting anti-GAD65Abs previously detected using commercial kit. The anti-anti-GAD65-antibodies reagent produced in our laboratories successfully identify anti-GAD65-Abs of type 1 diabetic patients previously detected with commercial reagent. (Med J Indones 2005; 14: 197-203)